Mídia, legislação penal emergencial e direitos fundamentais - Boldt, Raphael (2009)
Important characteristics of the postmodernity, the crisis of social contract and the rise of social fascism consolidate a punitive culture, common in all countries experiencing a process of (re)democratization and characterised by its authoritarian societies. In this context of increasing social exclusion, emerges a punitive discourse (re)produced through the mass media that legitimates unconstitutional punitive practices adopted by the state in its combat of criminality. The midiatic discourse promotes the fear and proposes to strengthen the criminal law as solution to the “violence issue”, despite the violation of historical fundamental rights. Although its capacity of deteriorate the fundamental rights protection spaces, the emergency criminal law emerges in response to the social demand for more repression, presented as the only way to achieve security. Besides an analysis of the midiatic discourse and its influence on the criminal law, the work proposes to establish relations between those and the fundamental rights, announcing the necessity of an alternative discourse, produced through a critical perspective – conciliating garantism and critical criminology to the philosophy of liberation – and intended to contention of the punitive power and to build an authentic humanist culture.